Challenges of Using Expansion Microscopy for Super‐resolved Imaging of Cellular Organelles. (11th November 2020) - Büttner, Maximilian; Lagerholm, Christoffer B.; Waithe, Dominic; Galiani, Silvia; Schliebs, Wolfgang; Erdmann, Ralf; Eggeling, Christian; Reglinski, Katharina
Abstract: Expansion microscopy (ExM) has been successfully used to improve the spatial resolution when imaging tissues by optical microscopy. In ExM, proteins of a fixed sample are crosslinked to a swellable acrylamide gel, which expands when incubated in water. Therefore, ExM allows enlarged subcellular structures to be resolved that would otherwise be hidden to standard confocal microscopy. Herein, we aim to validate ExM for the study of peroxisomes, mitochondria, nuclei and the plasma membrane. Upon comparison of the expansion factors of these cellular compartments in HEK293 cells within the same gel, we found significant differences, of a factor of above 2, in expansion factors. For peroxisomes, the expansion factor differed even between peroxisomal membrane and matrix marker; this underlines the need for a thorough validation of expansion factors of this powerful technique. We further give an overview of possible quantification methods for the determination of expansion factors of intracellular organelles, and we highlight some potentials and challenges. Abstract : In Expansion Microscopy (ExM) subcellular structures are imaged in isotropically expanded fixed samples, consequently allowing to resolve enlarged subcellular structures, otherwise hidden to standard microscopy. Upon comparison of the expansion factors of different cellular compartments in cells within the same gel, we found significant differences in expansion factors of a factor of above 2.